Módulo de integración entre le sistema de gestión de control del posgrado y el sistema de gestión de la Nueva Universidad - Menéndez Sarduy, Yorky (Universidad Central “Marta Abreu” de Las Villas, 2007)
En esta investigación, resultado de la necesidad de integrar el Sistema de Gestión del Control del Posgrado y el Sistema de Gestión de la Nueva Universidad, en la Universidad Central “Marta Abreu” de Las Villas, cuyo objetivo es modelar e implementar una capa de Servicios Web a través de la cual se interrelacionen estos sistemas mediante el uso del Software Libre, se abordan conceptos tales como: Software Libre, Aplicaciones Empresariales, J2EE, Model Driven Architecture (MDA), Arquitectura Orientada a Servicios (SOA) y Servicios Web, los que constituyen el sustento teórico de la investigación. La aplicación se realizó en 3 etapas, según la metodología MDA: la primera, destinada a su diseño; la segunda, a la generación de código; y la tercera, a la implementación del módulo. De esta forma se obtuvo un producto novedoso, robusto y escalable, que permite agilizar la integración entre los sistemas antes mencionados. En el trabajo se catalogan a AndroMDA y J2EE como herramientas idóneas para el desarrollo de Servicios Web; se muestra cómo un diseño que siga la metodología de MDA, permite obtener aplicaciones con un modelo extensible, flexible; y se pone de manifiesto como la integración entre el Sistema de Gestión del Control del Posgrado y el Sistema de Gestión de la Nueva Universidad a través de la implementación de un módulo basado en Servicios Web, permite agilizar, modernizar e informatizar los procesos directivos que en torno al posgrado, se realizan hoy en la Universidad Central “Marta Abreu” de las Villas. Abstract The present investigation, result of the integration necessity between the System of Management of the Control of the Postdegree and the System of Management of the New University, in the Central University “Marta Abreu” of Las Villas, whose objective is to model and implement a layer of Web Services through which these systems will interrelate by using Free Software, there are mentioned concepts such as: Free Software, Enterprise Applications, J2EE, Model Driven Architecture (MDA), Service Oriented Architecture (SOA) and Web Services. All of these concepts constitute the theoretical background of the current investigation. The application was developed into 3 stages, following the MDA methodology. The first stage dealt with the design of application. The second stage comprised the code generation and the third stage had to do with implementation of the module. In this

The present investigation, result of the integration necessity between the System of Management of the Control of the Postdegree and the System of Management of the New University, in the Central University “Marta Abreu” of Las Villas, whose objective is to model and implement a layer of Web Services through which these systems will interrelate by using Free Software, there are mentioned concepts such as: Free Software, Enterprise Applications, J2EE, Model Driven Architecture (MDA), Service Oriented Architecture (SOA) and Web Services. All of these concepts constitute the theoretical background of the current investigation. The application was developed into 3 stages, following the MDA methodology. The first stage dealt with the design of application. The second stage comprised the code generation and the third stage had to do with implementation of the module. In this work are catalogued AndroMDA and J2EE as suitable tools for the development of Web Services; showed like following the MDA methodology allow the obtainment of applications with an extensible model, flexible; and it is shown like integration between the System of Management of the Control of the Postdegree and the System of Management of the New University through the implementation of a module based on Services Web, allows to make agile, to modernize and to computerize the directive processes that around the postgraduate education, are made today in the Central University “Marta Abreu” of Las Villas
Keywords: Integración de Sistemas; Servicios Web; Software Libre; Educación de Posgrado; Universidad Central Marta Abreu de Las Villas (UCLV); Gestión Integrada; Postgrado; Sistemas de Control; Diseño; Software Libre; Universidad Central Marta Abreu de Las Villas